On Examination Malpractice in Nigeria Universities: Factor Analysis Determination - A.A. Akinrefon; O.C. Ikpah; A.O. Bamigbala; O.I. Adeniyi (University of Sofia, 2016)
Examination malpractice has become an epidemic in the nation educational system. This study seeks to assess the pattern of examination malpractice in higher institutions in Nigeria, their causes, effects and also proffer solutions. The sample size of the study was calculated using Yaro Yamane formula. The instrument used for the study was a questionnaire titled Causes and Effects of Examination Malpractice (CEEMQ). The data collected were analyzed using Factor analysis and Principal component analysis. The findings from the factor analysis in factor loading 1 revealed that items 13 (0.5998), 29 (0.6785) and item 8 (0.5062) are the major causes of examination malpractice. Factor loading 2 revealed that item 26 (0.6594) and item 25 (0.6342) are the major solutions and effects of exam malpractice. Analysis from factor loading 8 revealed that factor 15 (0.5154) is also a major cause of exam malpractice.